Neurological Consequences of Sphingosine Phosphate Lyase Insufficiency - Atreya, Krishan B.; Saba, Julie D. (Frontiers in Cellular Neuroscience, 2022)
In 2017, a previously unrecognized inborn error of metabolism caused by recessive mutations in SGPL1 was discovered by next generation sequencing. The disease features steroid-resistant nephrotic syndrome, adrenal insufficiency, and neurological defects. The latter include sensorineural hearing loss, cranial nerve defects, peripheral neuropathy, abnormal brain development, seizures and/or neurodegeneration. SGPL1 encodes the pyridoxal-5’-phosphate dependent enzyme sphingosine phosphate lyase (SPL), and the condition is now referred to as SPL insufficiency syndrome (SPLIS). SPL catalyzes the final step in the degradative pathway of sphingolipids in which the bioactive sphingolipid sphingosine-1-phosphate (S1P) is irreversibly degraded to a long chain aldehyde and ethanolamine phosphate. SPL guards the only exit point for sphingolipid metabolism, and its inactivation leads to accumulation of various types of sphingolipids which have structural roles in plasma membrane rafts, myelin, and signaling roles in cell cycle progression, vesicular trafficking, cell migration, and programmed cell death. In addition, the products of the SPL reaction have biological functions including the regulation of autophagic flux. In this review, the neurological manifestations of SPLIS will be described, and key insights regarding the neurological consequences of SPL insufficiency derived from the study of brain-specific SPL knockout mice and Drosophila mutants lacking SPL expression will be summarized.